A Note on Confidence Interval for the Power of the One Sample t Test. (17th August 2010) - Wong, A.
Abstract : In introductory statistics texts, the power of the test of a one-sample mean when the variance is known is widely discussed. However, when the variance is unknown, the power of the Student'st -test is seldom mentioned. In this note, a general methodology for obtaining inference concerning a scalar parameter of interest of any exponential family model is proposed. The method is then applied to the one-sample mean problem with unknown variance to obtain a( 1 − γ ) 100% confidence interval for the power of the Student'st -test that detects the difference( μ − μ 0 ) . The calculations require only the density and the cumulative distribution functions of the standard normal distribution. In addition, the methodology presented can also be applied to determine the required sample size when the effect size and the power of a sizeα test of mean are given.